Increasing prevalence and dissemination of invasive nontyphoidal Salmonella serotype Typhimurium with multidrug resistance in hospitalized patients from southern Brazil - Reis,Rafael Oliveira dos (2018)
ABSTRACT Introduction: Nontyphoidal Salmonella serotypes are the main cause of human food-borne infection, including several hospitalization cases in the developing countries. Aim: To detect the main serotypes and to characterize the antibiotic resistance of human non-enteric and enteric nontyphoidal Salmonella from clinical isolates in Brazil. Methods: Salmonella serotypes were identified by microbiological and molecular methods. Susceptibility testing to antibiotics was performed by agar disk diffusion. Real-time PCRs were carried out for the detection of the genus Salmonella as well as serotypes Typhimurium and Enteritidis. Results: A total of 307 nontyphoidal Salmonella were isolated from 289 different patients in a reference laboratory (LACEN-RS) from Southern Brazil in a six-year period (2010–2015). There were 45 isolates from emerging cases and 244 from sporadic cases in hospitalized patients. Non-enteric isolates were detected in 42.6% of the patients from sources such as urine, blood and other clinical fluids. Serological and PCR-specific tests demonstrated that Typhimurium (48.4%) and Enteritidis (18.3%) were the most frequent serotypes. Typhimurium isolates were generally resistant to three or more antibiotic classes, while Enteritidis isolates to one or two classes. Typhimurium was the most frequent serotype in all samples (48.4%), mainly among the hospitalized patients (55.6%), and presented the highest rates of multidrug resistance (59.3% of the isolates of this serotype). Further, the prevalence of this serotype increased along the years of the study in comparison to other nontyphoidal Salmonella serotypes. Conclusion: Greater public health attention should be given to prevent salmonellosis in the community and in hospital settings to reduce the rates of Typhimurium strains with multidrug resistance.